Access, timing and frequency of very early stroke rehabilitation – insights from the Baden-Wuerttemberg stroke registry. Issue 1 (December 2016) - Reuter, Björn; Gumbinger, Christoph; Sauer, Tamara; Wiethölter, Horst; Bruder, Ingo; Diehm, Curt; Ringleb, Peter; Hacke, Werner; Hennerici, Michael; Kern, Rolf
Abstract Background While the precise timing and intensity of very early rehabilitation (VER) after stroke onset is still under discussion, its beneficial effect on functional disability is generally accepted. The recently published randomized controlled AVERT trial indicated that patients with severe stroke might be more susceptible to harmful side effects of VER, which we hypothesized is contrary to current clinical practice. We analyzed the Baden-Wuerttemberg stroke registry to gain insight into the application of VER in acute ischemic stroke (IS) and intracerebral hemorrhage (ICH) in clinical practice. Methods 99, 753 IS patients and 8824 patients with ICH hospitalized from January 2008 to December 2012 were analyzed. Data on the access to physical therapy (PT), occupational therapy (OT), and speech therapy (ST), the time from admission to first contact with a therapist and the average number of therapy sessions during the first 7 days of admission are reported. Multiple logistic regression models adjusted for patient and treatment characteristics were carried out to investigate the influence of VER on clinical outcome. Results PT was applied in 90/87% (IS/ICH), OT in 63/57%, and ST in 70/65% of the study population. Therapy was mostly initiated within 24 h (PT 87/82%) or 48 h after admission (OT 91/89% and ST 93/90%). Percentages of patients under therapy and also the average number of therapy sessions were highest in those with a discharge modified Rankin Scale score of 2 to 5 and lowest in patients with complete recovery or death during hospitalization. The outcome analyses were fundamentally hindered due to biases by individual decision making regarding the application and frequency of VER. Conclusions While most patients had access to PT we noticed an undersupply of OT and ST. Only little differences were observed between patients with IS and ICH. The staff decisions for treatment seem to reflect attempts to optimize resources. Patients with either excellent or very unfavorable prognosis were less frequently assigned to VER and, if treated, received a lower average number of therapy sessions. On the contrary, severely disabled patients received VER at high frequency, although potentially harmful according to recent indications from the randomized controlled AVERT trial.